Mindful M&M's: Mindfulness and Parent Training for a Preschool Child With Disruptive Behavior Disorder. (December 2015) - Khaddouma, Alexander; Gordon, Kristina Coop; Bolden, Jennifer
Disruptive behavior problems are the primary reason for referral of preschool-aged children to mental health care settings and significantly interfere with social and academic functioning. Furthermore, when left untreated, disruptive behavior disorder may persist and cause impairments in social, academic, and occupational functioning in later developmental stages. Parent-based training programs are effective in ameliorating many symptoms of disruptive behavior disorders, but often neglect other child factors associated with disruptive behavior, such as deficits in emotion regulation. Mindfulness training may be an effective method for addressing these individual-level contributing factors underlying the child's disruptive behavior. At present, treatment outcome research on the efficacy of mindfulness training among preschool-aged children with disruptive behavior problems is highly limited. This case study examined the implementation of a two-part treatment consisting of a four-session parent-training program as well as four sessions of targeted mindfulness training for a preschool-aged child with disruptive behavior disorder. Treatment outcome data revealed significant gains, including improvements in emotion regulation and decreases in level of aggression, defiance, and sleep problems. Treatment gains were maintained at 6-month follow-up, along with further decreases in aggression, defiance, inattention, and hyperactivity, which resulted in no clinical-level symptoms at 6-months post-treatment. This case study demonstrates the potential efficacy of multi-strategy interventions for preschool-aged children with disruptive behavior problems and highlights mindfulness training as a promising adjunct to family-based interventions.